2022
DOI: 10.1371/journal.pone.0264685
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of body mass index and mid-upper arm circumference with anemia in non-pregnant women aged 19–49 years in Indonesia: Analysis of 2018 Basic Health Research data

Abstract: Background and objectives Anemia remains a major public health problem worldwide. This study examined the relationship between anemia and the nutritional status of non-pregnant women aged 19–49 years in Indonesia. Methods and study design The data were derived from the 2018 Basic Health Research Data of Indonesia. We used information from 11,471 non-pregnant women aged 19–49 years. The dependent variable was anemia (hemoglobin level <12 g/dL). The independent variable was women’s nutritional status, a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
1
9
0
2
Order By: Relevance
“…Based on the results of the study, it was found that there was a relationship between Middle-Upper Arm Circumference (MUAC) and the incidence of anemia in adolescent girls at SMAS PGRI 2 Banjarmasin. In line with the results of a study conducted (Nainggolan et al, 2022) it was found that the highest percentage of anemia was found in women who were underweight and low LILA. The results of another study from Ethiopia also reported that LILA > 23 cm reduced the incidence of anemia by 0.41 (Ghosh Id et al, 2019).…”
Section: B Relationship Of Middle-upper Arm Circumference (Muac) With...supporting
confidence: 84%
“…Based on the results of the study, it was found that there was a relationship between Middle-Upper Arm Circumference (MUAC) and the incidence of anemia in adolescent girls at SMAS PGRI 2 Banjarmasin. In line with the results of a study conducted (Nainggolan et al, 2022) it was found that the highest percentage of anemia was found in women who were underweight and low LILA. The results of another study from Ethiopia also reported that LILA > 23 cm reduced the incidence of anemia by 0.41 (Ghosh Id et al, 2019).…”
Section: B Relationship Of Middle-upper Arm Circumference (Muac) With...supporting
confidence: 84%
“…A study by Nguyen et al, published in the Journal of Nutrition in 2012, found that women with a BMI of less than 18.5 were more likely to be anaemic than those with a BMI greater than 25 [ 65 ]. Additionally, another study found that underweight women had a significantly higher risk of anaemia compared to normal-weight women [ 34 ]. However, it is important to note that BMI alone may not be a perfect indicator of nutritional status and overall health, and there may be other factors contributing to the relationship between BMI and anaemia.…”
Section: Discussionmentioning
confidence: 99%
“… 27 , 31 , 32 , 37 40 , 53 56 , 72 , 107 , 108 , 127 138 For most programmes, we derived methodological information from 89 programme reports or factsheets, 20 – 26 , 28 – 30 , 33 – 36 , 43 , 50 – 52 , 57 – 62 , 65 – 69 , 73 – 78 , 80 – 95 , 99 – 106 , 109 – 119 , 139 – 157 12 programme and/or governmental websites 41 – 48 , 63 , 70 , 157 – 159 and eight publications through our manual search of references. 49 , 64 , 71 , 96 , 120 , 123 , 160 , 161 We also received information about 11 programmes and five related publications 79 , 97 , 98 , 121 , 162 directly from national health and nutrition officials ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%